Remotely Supervised Exercise during the COVID-19 Pandemic versus in-Person-Supervised Exercise in Achieving Long-Term Adherence to a Healthy Lifestyle - Guillermo García Pérez de Sevilla (MDPI AG, 2021)
The World Health Organization’s global action plan on workers’ health establishes that occupational health services should carry out lifestyle interventions within the workplace, to prevent the development of non-communicable diseases. The objective of the study was to compare adherence to a healthy lifestyle six months after completion of a multi-component intervention with remotely supervised physical activity during the COVID-19 pandemic versus a multi-component intervention with in-person supervised physical exercise before the COVID-19 pandemic in university employees with unhealthy habits and predisposed to change. A prospective cohort study following the “Strengthening the Reporting of Observational studies in Epidemiology” (STROBE) guidelines was conducted, with two arms. Each multi-component intervention lasted for 18 weeks, and consisted of education on healthy habits, Mediterranean Diet (MedDiet)-based workshops, and a physical exercise program. Twenty-one middle-aged sedentary university employees with poor adherence to the MedDiet completed the study. Six months after completion of the intervention, both groups increased physical activity levels, adherence to the MedDiet, eating habits, health-promoting lifestyle, health responsibility, and health-related quality of life. There were no differences between groups in any of the variables analyzed. Therefore, remotely supervised physical exercise could be adequate to achieve long-term adherence to a healthy lifestyle in the same way as conventional face-to-face intervention, at least in a population willing to change.